Leveraging Digital Technology in Micro SMEs to Enhance Indonesia's Economic Prosperity - Utomo, Bambang; Setiyono, Yoyok Yekti (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study aims to analyse the use of digital technology to enhance the performance of micro, small, and medium enterprises (MSMEs) in Indonesia, identifying challenges, obstacles, and strategies to improve their competitiveness, productivity, and economic welfare through digital transformation. Design/Methodology/Approach:A qualitative approach with a descriptive-narrative method was used. Secondary data were gathered from websites, government reports, and journal articles, with 70% from Indonesia and 30% from international sources, to synthesise existing research on MSMEs’ digital technology adoption. Findings: Key barriers include limited digital literacy, inadequate infrastructure, and poor financial management practices. Despite these challenges, digital tools have expanded market access, improved transaction speed, and reduced costs. Strategies such as enhancing digital literacy, using e-commerce platforms, and increasing local government support have been crucial in supporting MSME growth. Originality/Value:This study provides insights into the strategies needed to strengthen MSME digital transformation in Indonesia, contributing to the development of policies and programs that empower MSMEs and boost their economic impact. These insights are valuable for policymakers, MSME leaders, and academics promoting digital adoption and economic resilience.